Some traffic characteristics of rural roads in Iraq - Al-Jameel Hamid Athab; Kadhim Ali Jihad (MATEC Web of Conferences, 2018)
Now a days, modeling traffic characteristics are very important in evaluating traffic facilitates such normal section, weaving and merging sections. Lane changing and lane utilization are important traffic characteristics that are widely studied. Therefore this study is focused on both of these. The lane changing behavior affects the capacity and safety of roads. The distribution of vehicles among lanes of roadway is important in terms of different aspects such as safety, traffic management and even the structural design of roads. Field data have been collected from different rural roads. Two types of roads were studied; two-lane section and three-lane section. The results of analysis for collected data indicate that the driver behaviour is different in terms of lane utilization in Iraq from other countries and the same behaviour was found for lane changes also. Compared to other countries, Iraq has the lowest lane utilization and highest frequency of lane changes. These data are urgently needed nowadays for calibrating and validating the sophisticated programs such as simulated microscopic programs. These data are so important to mimic the reality for driver behaviors in rural roadways.